An Analysis of Contemporary Social Welfare Issues - Laratta, Rosario (IntechOpen, 2016)
This book offers a sharp critique and a detailed analysis of some pernicious social welfare problems and the wide-ranging causes and consequences of those complex social issues on individuals, families, and communities. Unemployment, health-care disparities, teenage pregnancy, and intimate partner violence constitute the focus of this work. Based on empirical and historical analyses of primary and secondary data, the book provides a conceptual framework that facilitates the reader's understanding of how those social issues are interrelated. Each chapter offers some clear policy recommendations directed to address those social problems. Written by well-published scholars, this work will be of great interest not only to students majoring in the social and political sciences but also to academics and practitioners active in the field of social welfare, social policy, and social work.